Experimental study on VMD and its performance comparison with AGMD for treating copper-containing solution. (2nd November 2019) - Yang, Chaohuan; Peng, Xin; Zhao, Yajing; Wang, Xin; Cheng, Lan; Wang, Fang; Li, Yingdong; Li, Pingli
Highlights: Copper-containing solution was treated by VMD and AGMD process effectively. A comprehensive analysis of energy consumption was employed on VMD performance. The permeate flux and SHEC of VMD achieved 21.82 kg/m 2 -h and 674.5 kWh/m 3 . A stable VMD performance was achieved due to membrane stability. Abstract: This study investigated the performance of VMD and AGMD system for separating water from copper-containing solution. The impacts of various operating parameters and module parameters on VMD performance were studied in terms of permeate flux, rejection rate, total water production, specific thermal (electric) energy consumption, pressure drop and thermal efficiency. A relatively stable VMD performance with high rejection rate was achieved due to the chemical stability and the sponge-like structure of membrane. It was found that enhancing membrane length would increase thermal consumption and pressure drop simultaneously. Moreover, the membrane module with high packing density performed better in utilizing lower thermal energy. The maximum permeate flux and the minimum specific thermal energy consumption of VMD was 21.82 kg/m 2 -h and 674.5 kWh/m 3 respectively. Meanwhile, AGMD was superior for energy saving compared with VMD. In this study, VMD and AGMD process have shown the potential to treat copper-containing solution.